Moderating Role Of Supporting Work Environment On The Relationship Between Green Training And Development, Organizational Learning, Green Leadership, Employee Commitment And Green Performance Of Public Firms In Uae - Ansaari, Awad Abdelaziz Awad Nadir Al Ansaari (2024)
The issue of ecological sustainability has garnered significant attention from policymakers, environmental activists, and other individuals due to its long-term impact on the environment and daily life. For this reason, the role of public sector organizations is evident, as they have a major role to play in economic progression and social welfare while utilizing various natural resources that may contribute to environmental damage. For this reason, a substantial attention is required towards the green performance outlook for the public firms. The key purpose of this research is to examine the role of green leadership, green training and development, organizational learning, and organizational commitment towards green performance of public firms as working in the regional context of UAE. It further explores the moderating effect of supportive work environment on the relationship between green performance and its determinants. Using the quantitative research technique, the data was collected through a questionnaire technique where a valid sample of 284 respondents has been tested empirically. Moreover, data analysis has been conducted through descriptive statistics, correlational analysis, normality testing, and two step approach (i.e., measurement model and structural model). The results under measurement model reflect that there is no issue related to reliability and validity, internal consistency, convergent validity, and discriminant validity of the latent constructs.